Cuidado em território de exclusão social: covid-19 expõe marcas coloniais - Camilo, Claudia; Kahhale, Edna; Ferreira, Maria Luísa; Schveitzer, Mariana (Saúde e Sociedade, 2021)
A intersecção de gênero, raça e classe marca os territórios de exclusão social, especialmente em um país que carrega cicatrizes da colonialidade patriarcal e capitalista em suas estruturas, como é o caso do Brasil. O objetivo deste trabalho é compreender o cuidado em um desses territórios: a cidade de Cubatão/SP. A investigação, feita entre 2017 e 2020, incluiu a pandemia da covid-19, que sobrecarregou o cuidado no território. O método foi a pesquisa qualitativa, com oficinas, observação participante e entrevistas de profundidade. O cuidado era majoritariamente oferecido por mulheres, líderes comunitárias e profissionais da atenção primária do Sistema Único de Saúde. Para analisar os dados, utilizou-se a hermenêutica de profundidade. O referencial teórico foi a costura das teorias feministas da ética do cuidado, ecofeministas e interseccionais. A pesquisa revelou diversos desafios e potencialidades, como o cuidado ético-político, eixo da busca por justiça socioambiental. , Abstract The intersection of gender, race and class marks the territories of social exclusion, especially in a country that carries scars of a patriarchal and capitalist colonialism in its structures, as is the case in Brazil. The objective was to understand care in this territory of exclusion in Cubatão, São Paulo, Brazil. The research, conducted between 2017 and 2020, included the pandemic of COVID-19, which overloaded care in this territory. The method was qualitative research, with workshops, participant observation and in-depth interviews. The care delivered by community leaders and primary health care professionals from the Brazilian National Health System was mostly performed by women. For data analysis, depth hermeneutics was used. The theoretical reference was the perspective of feminists: ecofeminist, intersectional and Care Ethics. The study showed several challenges and the ethical-political care as an axis in the search for social and environmental justice.
http://www.scielo.br/scielo.php?script=sci_arttext&pid=S0104-12902021000200202&tlng=pt
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; brésil; care; covid-19; intersectionnalité; pandémie; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; travail; écoféminisme

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap